Synergistic Anti-Stress Effect of Selected Medicinal Plants in Mice - Bairagi, Vinod Ashokdas; Somavanshi, Deepak Balasaheb; Ahire, Yogesh Suresh; Nikam, Jayashri Sanjay; Jadhav, Swapnil Bandu; Hameed, Mohammed Saad Abdul; Patil, Chandrashekhar Dinkar; Shirode, Amol Mohan; Ikrama, Mohammad (International Journal of Pharmaceutical Investigation, 2026)
Background The discovery of efficacious anti-stress therapies is imperative, as chronic stress plays a substantial role in the development of numerous physical and mental health issues. Materials and Methods The present study evaluates the synergistic anti-stress effects of co-administration of Terminalia tomentosa and Withania somnifera in mice. In present study, aqueous extracts of Terminalia tomentosa and Withania somnifera were administered orally to mice individually and in combination. The mice were then subjected to chronic stress models, including the Restraint stress, Elevated Plus Maze (EPM), Open Field apparatus (OF), Light and Dark model (LD) to evaluate the efficacy of the treatments. The combined treatment of Terminalia tomentosa and Withania somnifera resulted in a significant increase in time spent in open arm, number of square travelled time in combination as compared to individual treatments. Results and Discussion Biochemical assays revealed that the combination therapy markedly reduced plasma corticosterone levels, a key stress hormone. Additionally, the antioxidant defense system was also enhanced, as evidenced by elevated activities of Glutathione (GSH) and Lipid Peroxides (LPO). Conclusion These results suggest that the combination of Terminalia tomentosa and Withania somnifera exerts a synergistic effect in mitigating stress, highlighting their potential as a natural therapeutic option for stress management.
Keywords: Anti-stress activity; LPO; Stress; Terminalia tomentosa; Withania somnifera